The Effect of Telecommunication Infrastructure on Economic Growth in the Six ASEAN Countries - Qurrota A'yun Pramitha Thoyibah; Lilik Sugiharti (Trunojoyo University of Madura, 2022)
Information and Communication Technology (ICT) as a facilitator of information between the government and the public by increasing network access and broadband services. Digital technology in ASEAN is worth up to US625 billion by 2030 (8 percent of ASEAN's annual GDP), which can be derived from increased efficiency, new products and services, etc. According to the World Bank (2015), the use of digital technology contributes to economic growth. This study aims to analyze the effect of Individual Internet Users Percentage, Mobile Cellular Subscriptions (Per 100 Persons), Fixed Broadband Subscriptions (Per 100 Persons), Government Expenditures and Labor on GDP Per Capita in six ASEAN Countries in 2011-2019. The type of data used in this research is secondary data from the World Bank which is processed by panel data regression method.The results show that simultaneously the input of the Neo-Classical growth theory is capital through telecommunications infrastructure which consists of the Percentage of Individual Internet Users, Mobile Cellular Subscriptions (Per 100 people), Fixed Broadband Subscriptions (Per 100 People), Government Expenditures and Labor have an effect significantly to economic growth in the six ASEAN countries. While partially all exogenous variables also show a significant effect on the endogenous variables of economic growth with varying values. Telecommunication infrastructure based on the indicators of Individual Internet User Percentage, Fixed Broadband Subscriptions (Per 100 Persons), Government Expenditures has a positive significance on economic growth. Surprising results on telecommunications infrastructure with indicators Mobile Cellular Subscriptions (Per 100 people) is a significant negative effect on economic growth. Labor shows that there is no effect but positive significance on economic growth.